1971
DOI: 10.1530/jrf.0.0250375
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Embryos Transferred Into the Iud-Bearing Uterus of the Rat

Abstract: Summary. An IUD is thought to exert a contraceptive effect either by (1) inducing the premature expulsion ofembryos, (2)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1972
1972
1978
1978

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…These observations indicated that PMNLs may be actively involved in the prevention of implantation in mice bearing an IUD. In other species, however, PMNLs are less evident, and it has been suggested that the acellular luminal contents might be embryotoxic (Parr, Schaedler & Hirsch, 1967;De Boer & Anderson, 1971;Smith, El Sahwi, Wilson & Moyer, 1971; see also Moyer, Shaw & Fu, 1976), thereby rendering embryos in some way abnormal before coming into contact with PMNLs.…”
Section: Introductionmentioning
confidence: 99%
“…These observations indicated that PMNLs may be actively involved in the prevention of implantation in mice bearing an IUD. In other species, however, PMNLs are less evident, and it has been suggested that the acellular luminal contents might be embryotoxic (Parr, Schaedler & Hirsch, 1967;De Boer & Anderson, 1971;Smith, El Sahwi, Wilson & Moyer, 1971; see also Moyer, Shaw & Fu, 1976), thereby rendering embryos in some way abnormal before coming into contact with PMNLs.…”
Section: Introductionmentioning
confidence: 99%